OPTIMIZING THE ROLE OF SHARED VISION AND HUMAN CAPITAL IN THE ERA OF CHANGE - Anggia Sari Lubis; Hardi Mulyono; Khalid Abdul Wahid; Mohd Nasir Ismail; Debbi Chyntia Ovami; Kartika (CV. RADJA PUBLIKA, 2024)
The sustainability and competitiveness of the company is supported by good human capital management. Human capital plays an important role in achieving the company's vision, mission and goals. The expression human capital was established to increase productivity and maintain competitive advantage as an important factor in expanding business and employee assets. Attention to human resources or human capital as one of the main production factors for most companies is often put second compared to other production factors such as capital, technology, and money. Many company leaders are less aware that the profits obtained by the company actually come from human capital. Human capital supported by a well-built shared vision will increase the company's ability to achieve its goals. Shared vision is a development tool to build organizational learning capabilities. This study examines the strategy for optimizing the role of shared vision and human capital in companies in an era of change. This type of research is a systematic literature review that will provide benefits in the implementation of shared vision and human capital in companies.